The Effect of Self-Efficacy and Motivation on the Effectiveness of the Lecturer’s Performance - Nugroho Budi R, Tiarto, (Jurnal Manajemen, 2020)
The purpose of this study was to determine how much influence self-efficacy and motivation have on the performance of Lecturers' in the College of Indonesian Aviation or Sekolah Tinggi Penerbangan Indonesia (STPI). The lecturers' self-efficacy decreases if it is not related to the disruptive era - industrial revolution 4.0. In applying Tridharma Perguruan Tinggi, lecturers have three main functions of education, research and community service. This research used an empirical approach with quantitative methods. Data collection was done by sampling with questionnaires and observation techniques. Through descriptive statistical analysis of the results of the variables Self-Efficacy (X1) and Motivation (X2) obtained from questionnaires for 30 respondents using the percentage of answers to 35 indicators. The same method in motivational variable data is for 12 indicators. Moreover, with the same method, the result data of lecturer performance variable (Y) towards 26 question indicators stated that lecturer performance at STPI is already good or high, it means that the correlation between two positive variables is solemnly strong. The result of this study indicated that self-efficacy and motivation are closely and strongly related to the effectiveness of the performance of STPI lecturers in the application of Higher Education Tridharma by STPI lecturers.